The Effect Of The Effectiveness Of The Implementation And Utilization Of Accounting Information Systems On Employee Performance - Husnaeni, Haifa Ghaidania; N.ARumiasih.; Rizqi, Muhammad Nur (Jurnal HARMONI: Jurnal Akuntansi dan Keuangan, 2023)
The sustainability and success of the company can be determined from the performance of employees. Employees are expected to be able to complete tasks and produce information in a timely, accurate and reliable manner. This research was conducted to determine the effect of the effectiveness of implementing accounting information systems and the use of accounting information systems on employee performance. This research was conducted at Bank Syariah Indonesia Bogor Sudirman Sub-Branch Office. The data source in this study used primary data obtained by distributing questionnaires to BSI KCP Bogor Sudirman employees. The sample taken is the total population, namely 30 respondents. Data analysis used descriptive statistical tests, data quality tests consisted of validity and reliability tests, and hypothesis testing using multiple linear regression analysis. The results showed that the effectiveness of implementing accounting information systems had no significant effect on employee performance, while the use of accounting information systems had a significant effect on employee performance and simultaneously or jointly had an effect on employee performance.